The etiology of stillbirth over 30 years: A cross‐sectional study in a tertiary referral unit. (29th September 2020) - O'Leary, Bobby D.; Walsh, Molly; Mooney, Eoghan E.; McAuliffe, Fionnuala M.; Knowles, Susan J.; Mahony, Rhona M.; Downey, Paul
Abstract: Introduction: Stillbirth remains an often unpredictable and devastating pregnancy outcome, and despite thorough investigation, the number of stillbirths attributable to unexplained causes remains high. Placental examination has become increasingly important where access to perinatal autopsy is limited. We aimed to examine the causes of stillbirth in normally formed infants over 30 years and whether a declining autopsy rate has affected our ability to determine a cause for stillbirths. Material and methods: All cases of normally formed singleton infants weighing ≥500 g that died prior to the onset of labor from 1989 to 2018 were examined. Trends for specific causes and uptake of perinatal autopsy were analyzed individually. Results: In all, 229 641 infants were delivered, with 840 stillbirths giving a rate of 3.66/1000. The rate of stillbirth declined from 4.84/1000 in 1989 to 2.51 in 2018 ( P < .001). There was no difference in the rate of stillbirth between nulliparous and multiparous women (4.25 vs 3.66 per 1000, P = .026). Deaths from placental abruption fell (1.13/1000 in 1989 to 0 in 2018, P < .001) and the relative contribution of placental abruption to the incidence of stillbirth also fell, from 23.3% (7/30) in 1989 to 0.0% (0/19) in 2018 ( P < .001). Stillbirth attributed to infection remained static (0.31/1000 in 1989 to 0.13 in 2018, P = .131), while a specific causal organism was found in 79.2% (42/53) of cases. Unexplained stillbirths decreased from 2.58/1000 (16/6200) in 1989 to 0.13 (1/7581) in 2018 ( P < .001) despite a fall in the uptake of perinatal autopsy (96.7% [29/30] in 1989 to 36.8% (7/19) in 2018; P < .001). Placental disease emerged as a significant cause of stillbirth from 2004 onwards (89.5% [17/19] in 2018). Conclusions: The present analysis is one of the largest single‐center studies on stillbirth published to date. Stillbirth rates have fallen across the study period across parity. A decrease in deaths secondary to placental abruption contributed largely to this. Infection‐related deaths are static; however, in one‐fifth of cases a causative organism was not found. Despite a decreasing autopsy rate, the number of unexplained stillbirths continues to fall as the importance of placental pathology is increasingly recognized.